Investigation of the Role of Helicobacter Pylori ın the Etiopathogenesis of Current Aphthous Stomatitis - Tsilosani, Nino; Khimshiashvili, Nino; Salia, Sophio (European Scientific Journal, ESJ, 2017)
Nowadays, etiopathogenesis of recurrent aphthous stomatitis is not fully understood. Chronic gastritis, gastric and duodenal ulcers, diseases associated with H. Pylori, often attend this oral pathology. It is acknowledged, that H. Pylori is a conditional-pathogenic microbe which is included in normal mucosalflora of the gastrointestinal tract and oral cavity. Oral cavity appears to be a secondary reservoir for the microorganisms and also a source of gastric reinfection after the eradicative treatment in case of gastroduodenal pathologies. H. Pylori has got ability to enhance aggressive factors and considerably reduce mucous membrane protective factors. In order to carry out further investigations on this issue, we have initiated observation on the patients with recurrent aphthous stomatitis. The aim of the study was to determine whether there is a correlation between Helicobacter Pylori infection and recurrent aphthous stomatitis. The results of the given investigation show there is a higher possibility that the role of Helicobacter Pylori in the etiopathogenesis of recurrent oral ulcers (aphthae) is significant.